The Effectiveness of the Contextual Teaching and Learning (CTL) Model in Improving Arabic Language Learning Outcomes of 9th-Grade Students at SMP it Dzatul Akmam Kandis - Abdillah Rofiif Fatin Ritonga; Munirul Abidin (Journal of Social Science Utilizing Technology, 2024)
Background. Arabic is a subject that presents unique challenges for students, including at SMP IT Dzatul Akmam Kandis, because apart from learning vocabulary and grammar, students also need to understand the cultural and historical context. To improve Arabic language learning outcomes for grade 9 students, the application of the Contextual Teaching and Learning model emerged as an interesting alternative. Purpose. This study aims to evaluate the effectiveness of the Contextual Teaching and Learning model in improving the Arabic language learning outcomes of 9th-grade students at SMP IT Dzatul Akmam Kandis. Method. This research uses a quantitative approach with a One Group Pretest-Posttest experimental design on 24 grade 9 students at SMP IT Dzatul Akmam Kandis, selected through Cluster Random Sampling. The data collection instrument in the form of an essay test showed that 20 of the 25 questions were valid, with high reliability (Cronbach's Alpha 0.918). The data obtained were normally distributed and met the assumption of homogeneity of variance. Results. The research results showed that the Paired-Samples T Test results showed a significant difference between the pretest (71.17) and posttest (86.17) scores with an increase of 15.00 points after implementing the Contextual Teaching and Learning model. This research proves the effectiveness of the CTL model in improving Arabic language learning outcomes for grade 9 students at SMP IT Dzatul Akmam Kandis. A contextual approach is proven to create more meaningful and relevant learning experiences. The implication is that the integration of real-life contexts in Arabic language teaching is very important to improve students' understanding and skills. Further research is recommended to examine the long-term effectiveness of the CTL model at various levels of education. Conclusion. This research shows that the Contextual Teaching and Learning learning model is effective in improving the Arabic language learning outcomes of grade 9 students at SMP IT Dzatul Akmam Kandis. The average student score increased from 71 to 86 after implementing the CTL model. The results of the Paired-Samples T Test show significant differences, proving that the contextual approach is able to improve students' understanding and ability to speak Arabic.